Designing inorganic-organic nanofibrous composite membrane for advanced safe Li-ion capacitors. (20th March 2020) - Liu, Weicui; Ju, Jingge; Deng, Nanping; Wang, Liyuan; Wang, Gang; Li, Lei; Kang, Weimin; Cheng, Bowen
Abstract: In this work, the inorganic-organic nanofibrous composite separators were successfully prepared for Li-ion capacitor (LIC) via wet-laid method using electro-blown spun inorganic alumina (Al2 O3 ) nanofibers and electrospun organic polyimide (PI) nanofibers as components. Benefitting from the synergistic action of fast ions transfer performance and outstanding fire-resistance offered by Al2 O3 nanofibers as well as heat-resistance and entangled force derived from PI nanofibers, the novel membranes exhibited excellent film forming property, outstanding flexibility and high ionic conductivity. Moreover, it delivered superior fire-resistance with dimensional stability after burning. It was discovered that the novel membranes prepared with 50 wt% Al2 O3 nanofibers showed better ionic conductivity of 2.71 × 10 −3 S cm −1 and broader electrochemical stability window of 5.3 V than those of commercial membranes. The LIC assembled with this novel separator reached the energy density of 12.5 Wh kg −1 even at the high power density of 15 kW kg −1 . In addition, this LIC presented a high energy density of 57.3 Wh kg −1 at the current density of 0.5 A g −1 and maintained a high cycle stability even after 10, 000 cycles. This study provided the design idea and experimental basis for the development of high-performance LIC separator.